2014
DOI: 10.4314/jasem.v18i2.25
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Extension Agents Commitment to the Agricultural Loans and Inputs Supply Programme on Special Rice Production in Delta State, Nigeria

Abstract: ABSTRACT:The study evaluated the activities of Extension agents on Agricultural Loans and Inputs Supply Programme participant farmers' rice output/income. Data were collected with the aid of questionnaire from 60Extension agents (participating in the ALIS programme) randomly selected from 6 LGAs (where the programme is being implemented) of Delta State. Data were also collected from 80 participant and 80 nonparticipant farmers' of the programme. Results of data analysis reveals that all the Extension agents ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 5 publications
2
3
0
Order By: Relevance
“…This shows that agricultural extension workers had reasonable experience in carrying out extension works and as such they would have been exposed to training on the use of web-based tools in the discharge of their duties as information experts. This study conforms with the assertions of who reported over 17 years of experience for the extension workers in Delta State, Nigeria while reported 15 years as the average years of experience among extension workers in Nigeria (Okwuokenye and Okoedo-Okojie, 2014;Davis et al, 2019)…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This shows that agricultural extension workers had reasonable experience in carrying out extension works and as such they would have been exposed to training on the use of web-based tools in the discharge of their duties as information experts. This study conforms with the assertions of who reported over 17 years of experience for the extension workers in Delta State, Nigeria while reported 15 years as the average years of experience among extension workers in Nigeria (Okwuokenye and Okoedo-Okojie, 2014;Davis et al, 2019)…”
Section: Resultssupporting
confidence: 91%
“…The finding shows that agricultural extension workers in the study area had moderate household size of about 6. The findings conform with the studies of which reported that agricultural extension workers in Nigeria had between low to moderate family size as compared to most farmers with, Results show that the mean annual income of agricultural extension workers in Nigeria based on the selected sample was approximately 1.432,280.00 (Ogunwande et al, 2018;Okwuokenye and Okoedo-Okojie, 2014). This shows that on average, an extension worker receives about N119, 356.66 per month as salary.…”
Section: Resultssupporting
confidence: 87%
“…Okuokenye & Okoedo-Okojie (2014) investigated activities of extension agents on agricultural loans and inputs supply programme of participant farmers’ rice output/income. Questionnaire served as the instrument of data collection from a sample of 60 randomly selected extension farmers and 80 participant and 80 non-participant farmers’.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The empirical review reveals that adequate empirical literature abound on agricultural financing through the extension services of ADP in Nigeria. Most of the studies agree that the ADPs have made significant impact on agricultural production in Nigeria, especially in the a areas of increased agricultural output and income as well as improved rural livelihood ( Adamu & Mohammed, 2009; Ammani et al , 2010; Okuokenye & Okoedo-Okojie, 2014; Olujenyo, 2006; Omonijo et al , 2014; and Ugwu, 2007). However, not all the objectives of the programme have been successful.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation